Knowledge engineering and knowledge management : 20th International Conference, EKAW 2016, Bologna, Italy, November 19-23, 2016, Proceedings /: 20th International Conference, EKAW 2016, Bologna, Italy, November 19-23, 2016, Proceedings. (2016) - Unknown
No abstract available